Translational repression of viral RNA mediates arbovirus persistence in mosquitoes - Talló-Parra, Marc; Puig-Torrents, Mireia; Pérez-Vilaró, Gemma; Pons, Sol Ribó; Hernández-Alias, Xavier; Mantica, Federica; Irimia, Manuel; Serrano, Luis; Díez, Juana (bioRxiv, 2025)
Persistent infection of mosquito cells is essential for the transmission of arboviruses, yet how these viruses produce sufficient progeny without compromising host cell fitness remains unclear. Arbovirus genomes exhibit suboptimal codon usage for both human and mosquito hosts, raising questions about how they achieve efficient translation in such distinct cellular environments. Using chikungunya virus (CHIKV) as a model, we conducted a temporal, genome-wide analysis of transcription, translation, and tRNA modifications in Aedes albopictus C6/36 cells. Unlike in human cells, CHIKV infection does not alter the tRNA modification landscape in mosquitoes to overcome codon bias, nor does it induce widespread degradation of host transcripts. Instead, viral persistence is marked by a progressive, virus-specific repression of CHIKV RNA translation, occurring alongside a recovery of host mRNA translation. This translational balance, maintained independently of the RNAi system, enables sustained viral production without major disruption to host gene expression. Our findings identify translational control as a central mechanism underlying persistent arbovirus infection in mosquito cells.